2012
DOI: 10.2174/157015912804143522
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal-glial Interactions Define the Role of Nitric Oxide in Neural Functional Processes

Abstract: Nitric oxide (NO) is a versatile cellular messenger performing a variety of physiologic and pathologic actions in most tissues. It is particularly important in the nervous system, where it is involved in multiple functions, as well as in neuropathology, when produced in excess. Several of these functions are based on interactions between NO produced by neurons and NO produced by glial cells, mainly astrocytes and microglia. The present paper briefly reviews some of these interactions, in particular those invol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 130 publications
3
12
0
Order By: Relevance
“…NO is a versatile molecule particularly important in the CNS, where it participates in synaptic plasticity, neurotransmitter release, and also in immune response. However, when produced in excess via iNOS by activated microglia, NO contributes to acute and chronic inflammation and causes neuronal cell death, directly or by its oxidation products, such as peroxynitrite, which is produced by the oxidation of NO with superoxide [63][64][65][66][67]. Elevated levels of pro-inflammatory cytokines, such as TNF-α, IFN-γ, IL-1β, IL-6, and IL-18, have also been shown in various inflammatory conditions and, in this regard, a recent study showed that the microalga Euglena tuba can counteract the increased levels of inflammatory cytokines in an LPS-induced model of systemic inflammation [27].…”
Section: Discussionmentioning
confidence: 99%
“…NO is a versatile molecule particularly important in the CNS, where it participates in synaptic plasticity, neurotransmitter release, and also in immune response. However, when produced in excess via iNOS by activated microglia, NO contributes to acute and chronic inflammation and causes neuronal cell death, directly or by its oxidation products, such as peroxynitrite, which is produced by the oxidation of NO with superoxide [63][64][65][66][67]. Elevated levels of pro-inflammatory cytokines, such as TNF-α, IFN-γ, IL-1β, IL-6, and IL-18, have also been shown in various inflammatory conditions and, in this regard, a recent study showed that the microalga Euglena tuba can counteract the increased levels of inflammatory cytokines in an LPS-induced model of systemic inflammation [27].…”
Section: Discussionmentioning
confidence: 99%
“…It was shown that increased synthesis of NO by microglia can lead to damage of neurons (Graber et al, 2012 ). iNOS is responsible for synthesis of nitric oxide in microglia (Contestabile et al, 2012 ). In vitro studies indicated NO-dependent microglial reactions in the form of death of neurons, especially under conditions of inflammation (Graber et al, 2012 ).…”
Section: Nitric Oxide In Pathogenesis Of Schizophreniamentioning
confidence: 99%
“…However, a full understanding of brain's physics and biochemistry comes not only from an integrated analysis of the cells within their networks, but also from the interactions of and feedback among the networks. Although in recent years studies on biochemical interactions among brain's networks have started to emerge [1][2][3][4][5][6][7], a good comprehension of the coupled mechano-electrochemical processes that either provide or diminish brain's functions is still lacking. This knowledge is critical in improving existing diagnostic and therapeutic protocols and developing better new ones.…”
Section: -Introductionmentioning
confidence: 99%
“…Figure 1 shows a schematic of those aspects of the neuro-glial-vascular unit that are of interest to this paper. A neuro-glial-vascular unit (also known in the literature as neurovascular unit) is made of a group of neurons and nearby astrocytes (glial cells) that are connected functionally to the endothelium and smooth muscles of the small blood vessels with the purpose of controlling the supply of cerebral blood needed for the proper functionality of the brain [2]. Astrocytes have at least one endfoot that is in contact with the vasculature, and it is believed that the endfeet of all astrocytes completely encompass all the cerebral vessels [4].…”
Section: -Introductionmentioning
confidence: 99%
See 1 more Smart Citation